Cirrhosis is Associated with an Increased 30‐Day Mortality After Venous Thromboembolism. Issue 7 (July 2015) - Søgaard, Kirstine Kobberøe; Horváth‐Puhó, Erzsébet; Montomoli, Jonathan; Vilstrup, Hendrik; Sørensen, Henrik Toft
Abstract : OBJECTIVES: : Patients with cirrhosis are at increased risk of venous thromboembolism (VTE), but the impact of cirrhosis on the clinical course following VTE is unclear. In a nationwide cohort study, we examined 30‐day mortality among patients with cirrhosis and VTE. METHODS: : We used Danish population‐based health‐care databases (1994–2011) to identify patients with incident VTE, i.e., deep venous thrombosis (DVT), pulmonary embolism (PE), and portal vein thrombosis (PVT). Among these, we identified 745 patients with cirrhosis and 3647 patients without cirrhosis (matched on gender, year of birth, calendar year of VTE diagnosis and VTE type). We assessed the 30‐day mortality risk among VTE patients with and without cirrhosis, and the mortality rate ratios (MRRs), using an adjusted Cox model with 95% confidence interval. We obtained information on immediate cause of death for patients who died within 30 days after VTE. RESULTS: : The 30‐day mortality risk for DVT was 7% for patients with cirrhosis and 3% for patients without cirrhosis. Corresponding PE‐related mortality risks were 35% and 16%, and PVT‐related mortality risks were 19% and 15%, respectively. The adjusted 30‐day MRRs were 2.17 (1.24–3.79) for DVT, 1.83 (1.30–2.56) for PE, and 1.30 (0.80–2.13) for PVT. Though overall mortality was higher in patients with cirrhosis than patients without cirrhosis, the proportions of deaths due to PE were similar among patients (25% and 24%, respectively). CONCLUSIONS: : Cirrhosis is a predictor for increased short‐term mortality following VTE, with PE as the most frequent cause of death.